Bioregeneration of spent activated carbon: Review of key factors and recent mathematical models of kinetics - Leong, K.-Y. (Chemical Industry Press, 2018)
The disposal of spent activated carbon (AC) will inevitably create secondary pollution. In overcoming this problem, the spent AC can be regenerated by means of biological approach. Bioregeneration is the phenomenon in which through the action of microorganisms, the adsorbed pollutants on the surface of the AC will be biodegraded and this enables further adsorption of pollutants to occur with time elapse. This review provides the challenges and perspectives for effective bioregeneration to occur in biological activated carbon (BAC) column. Owing to very few reported works on the bioregeneration rate in BAC column, emphasis is put forward on the recently developed models of bioregeneration kinetic in batch system. All in all, providing potential solutions in increasing the lifespan of AC and the enhancement of bioregeneration rate will definitely overcome the bottlenecks in spent AC bioregeneration. Â© 2017 Elsevier B.V.